Pengaruh Pelatihan, Pembinaan, dan Penggunaan Digital Marketing terhadap Perkembangan UMKM Produk Makanan Halal di Kecamatan Selaparang - Hardono, Hardono; Muslihun, Muslihun; Yusup, Muhammad; Amini, Titik Husnawati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
As part of their product marketing strategy, MSMEs receive digital marketing training aimed at expanding market reach and increasing consumer interest in the goods supplied. The limited reach of SME marketing, which needs a broader reach in orders for its products to reach customers, is what drives this study. Training, mentorship, and the use of media, including digital marketing, are therefore required. This study sought to ascertain if digital marketing (X3), mentorship (X2), and training (X1) may impact the growth of small, medium, and very small enterprises (Y) selling halal food goods in Selaparang District, Mataram City. 600 persons make up the population of this quantitative study, and 240 respondents from small, medium, and micro companies that provide halal food goods in Selaparang District, Mataram City, were chosen as samples using the Slovin method. The Statistical Package for the Social Sciences (SPSS) software version 25 was used to process the questionnaires that were sent and interview the respondents in order to collect data. The study's findings show that UMKM and UMKM in Selaparang District, Mataram City, significantly impact the growth of halal food items through training, mentorship, and digital marketing, indicating that H4 is acceptable. H1 is rejected because training has a negligible and minor impact on MSMEs' growth, but H2 and H3 are accepted because digital marketing's development and application have a substantial impact on MSMEs' development.